2014
DOI: 10.5231/psy.writ.2015.2104
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de un programa de alta precoz sobre las preocupaciones de los padres de niños prematuros

Abstract: El nacimiento de un niño prematuro supone un gran impacto emocional en los padres, especialmente cuando la hospitalización se prolonga por mucho tiempo. Los programas de alta precoz son una herramienta eficaz para facilitar la transición al domicilio, mostrando resultados beneficiosos. Sin embargo, pocos estudios se han centrado en conocer cuáles son los efectos de éstos en los momentos posteriores al alta hospitalaria, así como los cambios en la dinámica familiar asociados.El objetivo del presente estudio fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…A sua influencia pode ser positiva quanto negativa, evidenciando a importância de envolve-las no processo de preparo para a alta. No geral, é necessário considerar o entorno social, podendo ser visto como recurso que suporta e ajuda as mães, ou pelo contrario, pode ser negativo, pela reprovação dos cuidados prestados da mãe sobre a criança prematura, fazendo-a sentir incapaz de exercer corretamente a maternidade (44).…”
Section: Redes De Apoio Socialunclassified
“…A sua influencia pode ser positiva quanto negativa, evidenciando a importância de envolve-las no processo de preparo para a alta. No geral, é necessário considerar o entorno social, podendo ser visto como recurso que suporta e ajuda as mães, ou pelo contrario, pode ser negativo, pela reprovação dos cuidados prestados da mãe sobre a criança prematura, fazendo-a sentir incapaz de exercer corretamente a maternidade (44).…”
Section: Redes De Apoio Socialunclassified
“…Therefore, concern and complex emotions of parents are governed by trust, hope and joy felt in relation to the time in which discharge home occurs. Nevertheless, regarding the child's care, fear or anxiety are still present due to long term uncertainty of prematurity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a work concerning risk factors that increase risk for the mother's mental health and influence the children's development, the group of investigators concluded that stress, depression and anxiety are associated with socioeconomic problems, family conflicts and the lack of support networks, which affects parenting [31]. It is worth noting that very few studies have focused on knowing the effects or emotional sequelae of the parents in the time following hospital discharge of their children [18].…”
Section: Introductionmentioning
confidence: 99%